2008
DOI: 10.1088/0264-9381/25/14/145012
|View full text |Cite
|
Sign up to set email alerts
|

The Immirzi parameter and fermions with non-minimal coupling

Abstract: We clarify the role played by the Immirzi parameter in classical gravity coupled to fermions. Considering the general non-minimal coupling, we show that, although the torsion depends explicitly on the Immirzi parameter, in a suitable parametrization the effective action obtained by integrating out the spin-connection is independent of it. Thus the Immirzi parameter is not detectable in classical theory even after coupling of fermions.Recently, coupling of fermions to classical general relativity has attracted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 18 publications
3
57
0
Order By: Relevance
“…Indeed the leading order in a in the expansion of h ABC vanishes, as expected from the curvature formula above (11). Second, we do want n a to be like a normal vector whose norm gives the area of the surface.…”
Section: B Non-abelian Normalsmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed the leading order in a in the expansion of h ABC vanishes, as expected from the curvature formula above (11). Second, we do want n a to be like a normal vector whose norm gives the area of the surface.…”
Section: B Non-abelian Normalsmentioning
confidence: 84%
“…The issue of the coarse-graining or of the continuum limit of the theory and of its dynamics are related, first because a consistent theory of quantum gravity should solve the problem of perturbative non-renormalizability and second because a good theory of quantum gravity should describe all scales * Electronic address: christoph.charles@ens-lyon.fr † Electronic address: etera.livine@ens-lyon.fr 1 This new set of variables corresponds to a canonical transformation at the classical level and depends on a new dimensionless parameter, the Immirzi parameter. Classically, this parameter does not play any role in the equation of motion, at least in the vacuum case [10,11]. 2 The torsion exists generally in the context of twisted geometries but does not reflect to a genuine torsion of the spin-connection.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we allow all possible real values of α as introduced in [23] (see also [53]). We emphasize that we have parity invariance for all real α, even though some torsion components such as those written below consist of contributions of different parity behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Then it was noted that even in the classical theory of gravity, the new Holst term does influence field equations when fermions are minimally coupled [15]. This initiated discussion on the role played by the Immirzi parameter in classical gravity with fermions [16][17] [18][19] [20]. As originally observed in [15], the Immirzi parameter enters the coupling constant in front of the four-fermion interaction term of EC gravity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that measuring the strength of this interaction can provide a tool to estimate the value of the Immirzi parameter independently from the quantum theory of gravity. Although the subsequent investigations [18] [20] showed that the Immirzi parameter can be "hidden" in the parameters of more general, non-minimal coupling procedures, it should be stressed that the minimal coupling scheme has been historically successful in constructing models, which could withstand the rigors of experimental testing whenever such tests were feasible. The experimental successes of the standard model of particle physics and general theory of relativity seem to support the minimal approach.…”
Section: Introductionmentioning
confidence: 99%